2021
DOI: 10.1002/ar.24746
|View full text |Cite
|
Sign up to set email alerts
|

Scalp acupuncture enhances local brain regions functional activities and functional connections between cerebral hemispheres in acute ischemic stroke patients

Abstract: This study aimed to explore the changes in functional connections between cerebral hemispheres and local brain regions functional activities in patients with acute ischemic stroke (AIS) treated with International Standard Scalp Acupuncture (ISSA). Thirty patients with middle cerebral artery AIS in the dominant hemisphere were selected and randomly divided into two groups such as the control group and the scalp acupuncture group, with 15 patients in each group. Patients in the control group were treated with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 40 publications
(38 reference statements)
1
28
0
Order By: Relevance
“…For instance, previous studies have demonstrated that stroke can cause significant disturbances in the effective connectivity of motor areas (5,14,18). FC between the bilateral primary sensorimotor cortex was significantly decreased in patients with stroke (17,46). Using diffusion tensor imaging (DTI), patients with stroke also demonstrated a decrease in the interhemispheric fiber connections between the left and right motor cortex (33,47,48).…”
Section: Significant Changes In Vmhc In Patients With Strokementioning
confidence: 99%
See 3 more Smart Citations
“…For instance, previous studies have demonstrated that stroke can cause significant disturbances in the effective connectivity of motor areas (5,14,18). FC between the bilateral primary sensorimotor cortex was significantly decreased in patients with stroke (17,46). Using diffusion tensor imaging (DTI), patients with stroke also demonstrated a decrease in the interhemispheric fiber connections between the left and right motor cortex (33,47,48).…”
Section: Significant Changes In Vmhc In Patients With Strokementioning
confidence: 99%
“…Additionally, brain function recovery after stroke is always difficult to evaluate (12). Mounting evidence has suggested that the recovery of impaired behavioral function is accompanied by brain reorganization after effective treatment (13)(14)(15)(16)(17). Identifying stroke recovery processes by neuroimaging will benefit the selection of suitable treatments for stroke.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al (2020) reported that SA (ISSA_MS5, MS6, and MS7) enhances functional connections, especially between visual, cognitive, motor control, and planning-related brain regions in acute ischemic stroke patients, by using fMRI examination. Liu H. et al (2021) also reported that SA (ISSA_MS5, MS6, and MS7) could strengthen the functional activities related to sensory integration, language processing, 10.3389/fnins.2022.956854 and motor coordination of the dominant cerebral hemisphere and the motor control bilateral frontal lobe by using the fMRI examination. This present study may provide a scientific basis that SA can modulate the functional connections of brain regions related to the recovery of voluntary movement after brain damage.…”
Section: Discussionmentioning
confidence: 92%